Mechanical analysis methods for ultra-stiff CFRP from thin tapes - Persson, Mattias (My University, 2019)
Today there is an increasing demand for more environmentally friendly transport systems. One way to decrease the fuel consumption of vehicles such as cars or airplanes is to decrease their weight. By replacing heavy construction material such as steel, which is often used in for example cars, with a material that has just as good mechanical properties as steel but a fraction of the weight, more fuel efficient vehicles could be made. A carbon fibre composite material, constructed out of uniformly distributed ultrathin high modulus carbon fibre reinforced polymer tapes, with mechanical properties approaching those of steel but with about a fifth of the density is the subject of study for this Master’s thesis. The focus of the study was to construct mechanical analysis methods, i.e. models for predicting the stiffness and the strength in tensile loading, for the composite material that was manufactured and tested in an accompanying study with this thesis work. The model was constructed in the numerical computation environment MATLAB an shows good agreement with the experimental results obtained from the tensile tests. The model predicts the stiffness, strength and failure modes most likely to occur in the laminate when loaded in tension. The model takes in-situ effects into account. The first test and analysis results indicate great potential for the composite material as it exhibits tremendous mechanical properties even before the manufacturing has been perfected. The model also indicate failure of the laminate to initiate by tape pull-out followed by longitudinal tape fracture, and that transverse tape fracture is unlikely to occur for the simulated laminates.
Keywords: Materialvetenskap; Produktion; Maskinteknik; Materialteknik; Materials Science; Production; Mechanical Engineering; Materials Engineering